Washington Square [videorecording (DVD)] - Holland, Agnieszka, 1948-; Leigh, Jennifer Jason, 1962-; Finney, Albert, 1936-2019-; Chaplin, Ben; Smith, Maggie, 1934-; Ivey, Judith, 1951-; Garner, Jennifer, 1972-; James, Henry, 1843-1916 (Hollywood Pictures, Hollywood Pictures home Entertainment ; Distributed by Buena Vista Home Entertainment, 1997)
Catherine is a lonely young woman in search of happiness, until she is swept off her feet by the handsome Morris Townsend. Suspicious of the young man's true intentions, however, her controlling father threatens to disown Catherine if she follows her heart and marries against his wishes.